Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine. - Rosell, Daniel R.; Slifstein, Mark; Thompson, Judy; Xu, Xiaoyan; Perez-Rodriguez, M. Mercedes; McClure, Margaret M.; Hazlett, Erin A.; New, Antonia S.; Nabulsi, Nabeel; Huang, Yiyun; Carson, Richard E.; Siever, Larry S.; et al. (Psychopharmacology, 2023)
Rationale: Characterizing the neuroanatomical basis of serotonergic abnormalities in severe, chronic, impulsive aggression will allow for rational treatment selection, development of novel therapeutics, and biomarkers to identify at-risk individuals. Objectives: The aim of this study is to identify associations between regional serotonin transporter (5-HTT) availability and trait and state aggression, as well as response to the anti-aggressive effects of fluoxetine. Methods: We examined 5-HTT availability using positron emission tomography (PET) imaging with [11C]DASB in personality disordered patients with current physical intermittent explosive disorder (IED; n = 18), and healthy comparison participants (HC; n = 11), in the anterior cingulate cortex (ACC), amygdala (AMY), ventral striatum (VST), and midbrain (MID). After PET imaging, IED patients were treated with fluoxetine 20 mg daily (n = 9) or placebo (n = 6) for 12 weeks. Trait and state aggression, trait callousness, and childhood trauma were assessed. Results: In IED patients, trait aggression was positively associated with [11C]DASB binding in the ACC and VST; covarying for trait callousness and childhood trauma enhanced these correlations. Baseline state aggression was positively correlated with ACC [11C]DASB in IED patients. Greater baseline VST [11C]DASB binding predicted greater decreases in state aggression with fluoxetine treatment. Conclusions: Consistent with prior reports, ACC 5-HTT is related to trait aggression, and adjusting for factors related to proactive (callousness) and reactive (childhood trauma) aggression subtypes further resolves this relationship. Novel findings of the study include a better understanding of the association between regional 5-HTT availability and state aggression, and the involvement of VST 5-HTT with trait aggression, and with the anti-aggressive effects of fluoxetine.